The impact of primary care supported shielding on the risk of mortality in people vulnerable to COVID-19: English sentinel network matched cohort study. Issue 2 (August 2021) - Zarif, Azmaeen; Joy, Mark; Sherlock, Julian; Sheppard, James P; Byford, Rachel; Akinyemi, Oluwafunmi; Bankhead, Clare R; Deeks, Alexandra; Ferreira, Filipa; Jones, Nicholas; Liyanage, Harshana; McGagh, Dylan; et al.
Highlights: Shielding was associated with half the risk of mortality in the first 21 days. Risk of mortality was 54% higher in shielded over the remaining nine weeks. Risk of mortality in shielded group increased after the end of shielding. Our findings stimulate debate on potential implementation of shielding in future waves. Summary: Objectives: To mitigate risk of mortality from coronavirus 2019 infection (COVID-19), the UK government recommended 'shielding' of vulnerable people through self-isolation for 12 weeks. Methods: A retrospective cohort study using a nationally representative English primary care database comparing people aged >= 40 years who were recorded as being advised to shield using a fixed ratio of 1:1, matching to people with the same diagnoses not advised to shield ( n  = 77, 360 per group). Time-to-death was compared using Cox regression, reporting the hazard ratio (HR) of mortality between groups. A sensitivity analysis compared exact matched cohorts ( n  = 24, 752 shielded, n  = 61, 566 exact matches). Results: We found a time-varying HR of mortality between groups. In the first 21 days, the mortality risk in people shielding was half those not (HR = 0.50, 95%CI:0.41–0.59. p  < 0.0001). Over the remaining nine weeks, mortality risk was 54% higher in the shielded group (HR=1.54, 95%CI:1.41–1.70, p  < 0.0001). Beyond the shielding period, mortality risk was over two-and-a-half times higher in the shielded group (HR=2.61, 95%CI:2.38–2.87, p  < 0.0001). Conclusions: Shielding halved the risk of mortality for 21 days. Mortality risk became higher across the remainder of the shielding period, rising to two-and-a-half times greater post-shielding. Shielding may be beneficial in the next wave of COVID-19.